Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1902/jop.2006.050233
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Periodontal Disease and Number of Remaining Teeth Are Related to the Prevalence of Myocardial Infarction and Hypertension in a Study Based on 4,254 Subjects

Abstract: The severity of periodontal disease was related to HT independent of age but to the prevalence of MI in middle-aged subjects only. The number of diseased pockets was significantly related to HT only. On the other hand, the number of teeth was associated with the prevalence of MI independent of age but not to HT. These data support the view that oral health is related to cardiovascular disease in a dose-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
160
4
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(187 citation statements)
references
References 29 publications
13
160
4
6
Order By: Relevance
“…Our research showed a relationship between the number of lost teeth and MI, similarly to the studies by other authors [14,22,26,27]. Most recently, a linear relationship between tooth loss and the degree of arterial stiffness that differed depending on sex was suggested [28].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our research showed a relationship between the number of lost teeth and MI, similarly to the studies by other authors [14,22,26,27]. Most recently, a linear relationship between tooth loss and the degree of arterial stiffness that differed depending on sex was suggested [28].…”
Section: Discussionsupporting
confidence: 91%
“…It is also one of the few works that have assessed the relationship between the number of teeth and MI [11,17,22,26,27,30]. The authors demonstrated a strong positive association between the extent of periodontitis and MI, independent of classical CVD risk factors, including tobacco smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However Elter [31] observed increased risk of cardiovascular disease in patients with significant edentulous area and high Clinical Attachment Level parameters. Holmlund [32] showed relevant correlation between the myocardial infarction and the average number of missing teeth in group of 3352 people, who required periodontal treatment and presented themselves with that problem at the dental office. Also Desvarieux [24] and other authors stated the positive correlation between the number of lost teeth and the frequency of atheromatous plaque presence in cervical arteries, detected in ultrasound [25,31].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found a highly significant relationship between periodontitis and hypertension after adjustment for age, physical inactivity, heredity and other periodontal parameters ( Table 3). Periodontal disease [12]. According to Engstrom, hypertension was also significantly associated with periodontal pocket values greater than or equal to 5 mm after adjustment for age, sex, smoking and the number of remaining teeth (OR = 1.76 and [1.14 -2.72]) [13].…”
Section: Discussionmentioning
confidence: 99%